2021
DOI: 10.3389/fpsyg.2021.622529
|View full text |Cite
|
Sign up to set email alerts
|

“Oh, My God! My Season Is Over!” COVID-19 and Regulation of the Psychological Response in Spanish High-Performance Athletes

Abstract: Background: In an unprecedented situation of interruption of the sporting dynamics, the world of sport is going through a series of adaptations necessary to continue functioning despite coronavirus disease 2019 (COVID-19). More than ever, athletes are facing a different challenge, a source of discomfort and uncertainty, and one that absolutely alters not only sports calendars, but also trajectories, progressions, and approaches to sports life. Therefore, it is necessary to identify the levels of psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
7
1
2
Order By: Relevance
“…Em relação à faixa etária, os atletas mais jovens exibiram graus de ansiedade, insegurança e pensamentos catastróficos superiores aos dos veteranos. Tal tendência denota que a experiência de vida, o acúmulo de vivências pessoais e o tempo de prática são hipoteticamente capazes de robustecerem a resiliência e o otimismo (González-Hernández, 2021). Em compensação, os veteranos sem programas de treinamento específicos e com monitoração frequente pelos treinadores e preparadores físicos demonstraram quedas na motivação mais intensas do que as observadas nos novatos (Ruffault, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em relação à faixa etária, os atletas mais jovens exibiram graus de ansiedade, insegurança e pensamentos catastróficos superiores aos dos veteranos. Tal tendência denota que a experiência de vida, o acúmulo de vivências pessoais e o tempo de prática são hipoteticamente capazes de robustecerem a resiliência e o otimismo (González-Hernández, 2021). Em compensação, os veteranos sem programas de treinamento específicos e com monitoração frequente pelos treinadores e preparadores físicos demonstraram quedas na motivação mais intensas do que as observadas nos novatos (Ruffault, 2020).…”
Section: Resultsunclassified
“…Não foram registradas diferenças nos escores totais dos testes de ansiedade aplicados a atletas contaminados e não contaminados por Covid-19. A mesma tendência se Uma característica demográfica dos estudos foi a de que a maior parte deles foi efetuada na América do Norte e em nações da Europa (Graupensperger, 2020;Håkansson, 2020;Ozen, 2020;Leguizamo, 2021;Szczypińska, 2021;Şenışık, 2021;diCagno, 2020;Turgut, 2020;Demarie, 2020;Fiorilli, 2021;Facer-Childs, 2021;diFronso, 2020;Morbée, 2021;Ungur&Karagozoğlu, 2021;Özen, 2021;Ruffault, 2020;Lautenbach, 2021;Pons, 2020;Martínez-González, 2021;González-Hernández, 2021;Roberts & Lane, 2021;Sanborn, 2021). Além deles, pesquisas aconteceram, em menor grau, no Irã, China e África do Sul.…”
Section: Resultsunclassified
“…Thus, we see in the current study that Polish athletes, especially women, have a stronger response to the lockdown situation, which should receive particular interest. Numerous studies show that athletes all around the world experienced a decrease in mental wellbeing, an increased level of stress, anxiety, depressive symptoms and feelings of anger, confusion during the first lockdown, and women and individual sports representatives seem to have the highest costs of the problematic situation of pandemic [1,9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, many researchers have identified how the coping capacity and lived experiences of elite and amateur athletes have had different repercussions on their physical and mental health, as well as alterations in sleep and nutrition during confinement ( 21 , 22 ). Some authors have shown that athletes tended to live the experiences associated with the pandemic in different ways, with the increase in anxiety and stress levels being most reported, especially in amateur athletes ( 23 ), mainly due to the fear of being infected ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%